Investigation of thin films deposition into porous material - Sedláková, L.; Kolouch, A.; Hladík, J.; Spatenka, P. (Вопросы атомной науки и техники, 2006)
Although the direct contact of the treated material with the plasma is assumed by the plasma community as a necessary condition of successful plasma treatment, several references mention penetration of active species into the porous material. Hydrophylity enhancement has been observed even inside porous material. The aim of this study is experimental investigation of plasma. This work is aimed to experimental investigation of thin layers deposition on porous substrates. The porous substrate was simulated with a specimen made from two glass wafers, on the margins of which two difference strips of varying thickness were placed. These strips define the thickness of the slot in the middle. After the deposition the substrate was decomposed and the film deposited inner walls of the glass wafers was investigated. Layers were deposited by method PECVD used RF plasma from gas C2H2. The film thickness was measured in dependence on the distance from the margin into the centre of the slab by optical profilometer. Penetration dept was tested in dependence on deposition conditions and geometric configuration of the substrate. Depending on deposition conditions, the film deposition was observed even on the whole substrate.